The One Health approach to face bacterial resistance to antibiotics in livestock production - Almeida da Silva, Rafael (2025)
The bacterial resistance to antibiotics (AMR-Bacteria) is one of the main global health problems. In 2019 alone, it was estimated that 1.27 million people died due to complications from resistant bacterial diseases. The One Health approach is the primary strategy in addressing AMR-Bacteria. Thus, this essay aimed to reflect on the application of the One Health approach in addressing AMR-Bacteria within the scope of agriculture. AMR-Bacteria is partially related to the intensive production of animal-origin foods. One of the main challenges for implementing the approach is the lack of communication among stakeholders. The solution to this impasse involves transdisciplinary training to form research networks and develop surveillance tools. One Health presupposes negotiation to build sustainable public policies. The search for strategies to address AMR-Bacteria involves considering the balance between the economic issue of food production, the physical well-being of animals, and the effects on the environment. Those wishing to implement the approach must form teams, combine methods and techniques, and involve different stakeholders. Through the lens of One Health, one can better understand how human actions contribute to the spread of AMR-Bacteria.